HISTOLOGY AND PROFILE OF AGRANULOCYTE OF BALI CATTLE WITH CONVENTIONAL REARED SYSTEM - Utami, Putri; Suwiti, Ni Ketut; Suartha, I Nyoman; Setiasih, Ni Luh Eka; Susari, Ni Nyoman Werdi; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana, 2024)
Bali cattle are one of the livestock that are currently widely bred by farmers in Bali. Generally, Bali cattle are raised conventionally or traditionally and pay less attention to the health of the cattle. This situation can affect the immune system of Bali cattle, especially white blood cells that play a role in the immune system such as lymphocytes and monocytes. This study aims to determine the histomorphometry of white blood cells agranulocytes lymphocytes and monocytes in Bali cattle with conventional reared system. Blood test preparations were taken from 30 cows in Bulian Village, Kubutambahan Subdistrict, Buleleng Regency, Bali. Fixation and staining using MDT IndoReagen®. Measurements were made using the EP View application connected to a microscope with 1000x magnification. Calculation of the number of lymphocytes and monocytes by counting up to 100 white blood cells. The results showed that the histomorphology of lymphocytes has an irregular shape, a thin blue-purplish cytoplasm, with a nucleus that almost fills the cytoplasm. Lymphocytes have an area of 17.56 ± 2.37 µm2, perimeter of 14.7 ± 1.14 µm, and diameter of 4.71 ± 0.33 µm. The histomorphology of monocytes has an irregular shape, the cytoplasm is not granular and the nucleus is found hollow. Monocytes have an area of 22.59±5.09 µm2, perimeter of 16.69±2.37 µm, and diameter of 5.19±0.66 µm. Further research is needed on the histomorphometry of granulocytes: neutrophils, basophils, and eosinophils of Bali cattle.